2021
DOI: 10.1093/mnras/stab3620
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric mass loss and stellar wind effects in young and old systems – II. Is TOI-942 the past of TOI-421 system?

Abstract: The two planetary systems TOI-942 and TOI-421 share many similar characteristics, apart from their ages (50 Myr and 9 Gyr). Each of the stars hosts two sub-Neptune-like planets at similar orbits and in similar mass ranges. In this paper, we aim to investigate whether the similarity of the host stars and configuration of the planetary systems can be taken as proof that the two systems were formed and evolved in a similar way. In paper I of this series, we performed a comparative study of these two systems using… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Observed exoplanet samples typically do not allow to infer the past activity history of the host star, with the possible exception of some multi-planet systems (e.g. Kubyshkina et al 2019bKubyshkina et al ,a, 2022. Therefore, observed samples will typically have a spread of stellar activity histories, whose effect we described in the results section.…”
Section: Discussionmentioning
confidence: 99%
“…Observed exoplanet samples typically do not allow to infer the past activity history of the host star, with the possible exception of some multi-planet systems (e.g. Kubyshkina et al 2019bKubyshkina et al ,a, 2022. Therefore, observed samples will typically have a spread of stellar activity histories, whose effect we described in the results section.…”
Section: Discussionmentioning
confidence: 99%
“…Koskinen et al Fig. 3 Evolution of planetary radii (solid lines and the left Y-axis) and atmospheric mass fractions (dash-dotted lines and the right Y-axis) with time for planets of different masses (colour-coded in the legend) evolving at ∼ 0.0909 AU orbit around a solar mass star, as predicted by atmospheric evolution models by Kubyshkina et al (2022b). The initial atmospheric mass fractions were set according to the approximation by Mordasini (2020) 2022; Huang et al 2023).…”
Section: Atmospheric Evolution: From Giant Planets To Super-earthsmentioning
confidence: 97%
“…The majority of recent studies (e.g. Baraffe et al 2004;Fortney and Nettelmann 2010;Lopez et al 2012;Lopez and Fortney 2014;Jin et al 2014;Mordasini et al 2015;Howe and Burrows 2015;Chen and Rogers 2016;Kubyshkina et al 2020Kubyshkina et al , 2022bEmsenhuber et al 2021;Gu and Chen 2023) tackle this problem by considering the hydrogen-dominated atmosphere on top of the inert solid core (which is typically assumed to be the mixture of silicates and metals but can have a more complex structure including ice/ocean layers; e.g. Valencia et al 2006;Dorn et al 2017;Venturini et al 2020).…”
Section: Atmospheric Evolution: From Giant Planets To Super-earthsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we aim at quantifying the impact of atmospheric mass loss onto the observed MR distribution of planets across a wide range of masses. To this end, we employ an atmospheric evolution framework combining realistic hydrodynamic escape and planetary thermal evolution (Kubyshkina & Vidotto 2021;Kubyshkina et al 2022) applying it to a grid of planets in the 1-110 M ⊕ range on various orbits corresponding to planetary equilibrium temperatures (T eq ) not lower than 500 K (∼2.5-75 days). In particular, we aim at outlining the role played by the initial atmospheric parameters at formation and by atmospheric escape processes as a function of system parameters.…”
Section: Introductionmentioning
confidence: 99%